El juego simbólico y las habilidades sociales en los niños de la Institución Educativa Inicial N° 386 Bellavista Callaru, Yavari 2022 - Sampayo Chanchari, Liz Magaly (2024)
The main purpose of this research was to examine the degree of connection between symbolic play and social skills in children enrolled in the Initial Educational Institution N°386 Bellavista Callaru, during the year 2022. To achieve this purpose, an approach was applied oriented towards relationships and a non-experimental, field-type research design was implemented, with a correlational approach and transectional nature. The population under study included all boys and girls enrolled in the Initial Educational Institution No. 386. A full sample of 61 participants was selected to carry out the analysis. The methodology used included observation, in which an observation guide was used as a tool to collect data, which were subsequently validated by experts in the field. The research hypothesis, which establishes that the application of symbolic play is directly related to children's social skills, was supported by the statistical analysis. The Student's t statistic value (9.6066) and the pvalue (0.000) support the existence of a significant relationship, rejecting the null hypothesis